Prospects for use of extended reality technology for ship passenger evacuation simulation - Vukelić, Goran, inženjer strojarstva (Array, 2021)
Safety of passengers on ships is usually investigated based on data available from post-accident reports, experimental research and/or numerical modelling of emergencies. As for the numerical modelling, ship passenger evacuation falls within a greater set of pedestrian evacuation research in which extended reality (XR) technology is playing important role lately. However, XR still strives to find its place in the modelling of ship passenger evacuation. This paper brings review of literature published on the topic of XR in pedestrian evacuation with special focus on the use of these technologies (e.g. virtual reality, augmented reality) in shipping industry. Findings are put in the context of IMO’s guidelines for evacuation analysis and prospect for use of XR for ship passenger evacuation simulation are presented.